Experimental investigation on seismic performance of the double‐superimposed shear wall with different vertical connections. (30th January 2022) - Meng, Longfei; Zhu, Lihua; Sun, Rui; Su, Hao; Ye, Yanhua; Xu, Lujun
Abstract: This study investigated the seismic performances of double‐superimposed shear walls (DSSWs). Two types of vertical connections were proposed and investigated for the double‐superimposed wall system. Both vertical connections contain a 400 mm wide concealed column; one is prefabricated connection and the other is a 400 mm thick cast‐in‐place connection. Four samples considering the cast‐in‐place concrete and vertical connections are tested cyclically. The damage and hysteresis characteristics, stiffness, ductility, and energy dissipation capacity of the specimens were analyzed. The failure mode of four spliced walls was bending‐shear failure, and all the walls show good seismic performance. The cast in situ connections with 400 mm thickness performed as well as the prefabricated connections. Then, the seismic performance indicators of DSSWs cast with self‐compacting concrete (SCC) are significantly enhanced compared with those of normal concrete shear walls. The use of SCC and cast‐in‐place vertical connections with 400 mm thickness is recommended, which is more convenient for construction in double‐superimposed wall systems. Furthermore, this study established the calculation models of the bearing capacity, and the calculation results agreed well with the experimental results.